SISTEM PENGONTROLAN PERSEDIAAN BARANG DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) MENGGUNAKAN ALGORITMA GENETIKA (Studi Kasus Gundaling Farm) - Nababan, Darsono (Journal Information System Development (ISD), 2017)
The problem of emphasis on the cost of spending on the need for ordering within a company is very complex where the company demands a very optimal achievement that will lead to a huge profit for the company. Gundaling Farm is a company engaged in the business of producing and selling cow's milk is always trying as much as possible to meet customer demand. In this research used Economic Order Quantity (EOQ) method with a genetic algorithm to solve supply problem on Pt.Gundaling Farm. This research is expected to help PT.Gundaling Farm to consider and determine the policy in inventory control activities in order to run more effectively and efficiently. EOQ is the quantity of goods that can be obtained with a minimal cost, or often said to be the optimal amount of purchases. So by applying EOQ method, PT.Gundaling Farm will know how many order (quantity order) goods and when PT.Gundaling Farm should re-order goods during the period 2015. Thus PT.Gundaling Farm can optimize the cost of inventory to be spent on goods.Keywords: inventory, goods, Economic Order Quantity (EOQ).algorithm, genetic